Women’s work–family conflict and its consequences in commuter marriages: The moderating role of spouses’ family commitment in a dyad analysis - Wu, Hsin-Pei; Wang, Yu-Mei (Frontiers in Psychology, 2022)
This study explored work‐family conflict and its consequences on job, family, and marriage satisfaction among stay-at-home wives in commuter couples by testing the moderating effect of commuters' family (parental, marital, and household) commitment. Commuter marriages are common among well-educated and employed members of modern society. Data from 120 dual‐earner and non-cohabitating couples were collected by using convenience sampling. The analytical approach of the actor-partner interdependence model was adopted. The results reveal that stay-at-home wives perceived more job dissatisfaction than cohabiting wives due to work-to-family conflicts and perceived more job, family, and marriage dissatisfaction caused by family-to-work conflicts. Moreover, the partner moderating effect of commuters’ family commitment as spousal support reversed the negative relationship between stay-at-home wives' family-to-work conflicts and family satisfaction.